If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -3 + x + -6 = 6y + -9 Reorder the terms: -3 + -6 + x + 4y = 6y + -9 Combine like terms: -3 + -6 = -9 -9 + x + 4y = 6y + -9 Reorder the terms: -9 + x + 4y = -9 + 6y Add '9' to each side of the equation. -9 + x + 9 + 4y = -9 + 9 + 6y Reorder the terms: -9 + 9 + x + 4y = -9 + 9 + 6y Combine like terms: -9 + 9 = 0 0 + x + 4y = -9 + 9 + 6y x + 4y = -9 + 9 + 6y Combine like terms: -9 + 9 = 0 x + 4y = 0 + 6y x + 4y = 6y Solving x + 4y = 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. x + 4y + -4y = 6y + -4y Combine like terms: 4y + -4y = 0 x + 0 = 6y + -4y x = 6y + -4y Combine like terms: 6y + -4y = 2y x = 2y Simplifying x = 2y
| 12w+30=20 | | -60=-6(x-3) | | x+(x+5)+3x+(3x-3)=114 | | X^2-94x-7200=0 | | X^2-94x-720=0 | | 41.9x^2-45.9x+11.48=0 | | 6x+3=10+4x | | C=24+15d | | 20/35=21/x | | 2x/6=2 | | 3x+10=42-10x | | -15+b=-9 | | x*0.08=3 | | 3+v=8 | | 6(x+6)=8x+5-2x+31 | | 2sin^2(3x)+sinx-1=0 | | 45z=pz-v | | (2x-11)(-5-7)=0 | | 4.5=0.08x | | 8+2(4x-6)=6-5(2x+1) | | 1+2=2+3 | | 3xy-12xy+18x-2(xy+5x)= | | 6+2x=26+6x | | f(x)=2x^2-24x+73 | | 8xsquared-4x=0 | | 3xy-12xy+18x= | | -32n=-48 | | 6-2x=26+6x | | -3(2x-2)=-18 | | 8a+7a=5(a-8)+6(a+2) | | X+(X*.115)=2.89 | | -6+3(b-5)=8(-4b-7) |